تطوير ريادة الأعمال كآلية لتحقيق النمو الاقتصادي في الجزائر دراسة قياسية للفترة 2001-2020 - بلوم, سعيدة; شاهد, عبد الحكيم (جامعة الوادي - University of Eloued, 2023)
This study aimed to measure the impact of entrepreneurship on economic growth in Algeria during the period from 2001 to 2020, by building a standard model that includes the number of small and medium enterprises and the percentage of total employment as two independent variables that express entrepreneurship and GDP as a dependent variable that expresses growth The study found that there is a positive effect of the independent variables (number of small and medium-sized enterprises and the percentage of total employment) on the dependent variable (GDP), which means that the increase in the number of small and medium-sized enterprises and the percentage of total employment by 1% will lead, respectively, to a rise in the growth rate of GDP by 0.63% and 3.26% for Algeria during the period from 2001 to 2020.
Entrepreneurship development as a mechanism to achieve economic development in Algeria A standard study for the period 2001-2020
مقال
Keywords: ريادة أعمال ; مؤسسات صغيرة ; نسبة تشغيل ; ناتج محلي إجمالي ; نم ; اقتصادي: entrepreneurship, small and medium enterprises, employment rate, GDP, economic growth.